2017
DOI: 10.14687/jhs.v14i1.4377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of group counseling on happiness, life satisfaction and positive-negative affect: A mixed method study

Abstract: The aim of this study is to investigate the effects of a group counselling programme on happiness, life satisfaction and positive-negative affect of guidance and psychological counselling department students. The group members consisted of 28 (18 females, 10 males). Group counselling programme was applied once a week for 8 weeks. Quantitative analysis of the study was performed using Wilcoxon Signed Rank Test and qualitative analysis was performed by content analysis of the focus group interviews and student e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…JS. With a view to understanding and gaining the knowledge for finding out the relationship between W to FC and JS in a better way, it has been explored in various occupations, fields and even different cultures (Rahman et al, 2019(Rahman et al, , 2018Bakalım and Karçkay, 2017;Kalliath and Kalliath, 2013;Anafarta, 2011 association between W to FC and satisfaction. Different meta-analyses also showed that W to FC harms satisfaction (life, job and family).…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…JS. With a view to understanding and gaining the knowledge for finding out the relationship between W to FC and JS in a better way, it has been explored in various occupations, fields and even different cultures (Rahman et al, 2019(Rahman et al, , 2018Bakalım and Karçkay, 2017;Kalliath and Kalliath, 2013;Anafarta, 2011 association between W to FC and satisfaction. Different meta-analyses also showed that W to FC harms satisfaction (life, job and family).…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
“…JS. With a view to understanding and gaining the knowledge for finding out the relationship between W to FC and JS in a better way, it has been explored in various occupations, fields and even different cultures (Rahman et al, 2019(Rahman et al, , 2018Bakalım and Karçkay, 2017;Kalliath and Kalliath, 2013;Anafarta, 2011). For example, Cortese et al (2010) conducted a descriptive correlation study based on 351 professional nurses in Italy, to show the causal relationship between the antecedents of W to FC and satisfaction and found a negative association between W to FC and satisfaction.…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
“…This study explored the process involved in the therapeutic healing of mirror effects from the perspective of those who experienced that process. The theoretical justification for mirror effects through action insight is grounded in group counselling (Bakalım & Karçkay, 2017), whereas the theoretical justification for the application of action and experiential learning in the context of counselling education is based on adopting the philosophy, concept, and skills of group counselling therapies. This very combination can make theory building endlessly fascinating.…”
Section: Resultsmentioning
confidence: 99%
“…Work conflict dapat menimbulkan dampak negatif bagi dirinya sendiri, keluarga, dan organisasi dalam hal menyeimbangkan waktu dan peran (Bakalım & Karçkay, 2017).…”
Section: Pembahasan Hasil Penelitianunclassified